2018
DOI: 10.1097/phh.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Community Priorities for Hospital-Based Prevention Initiatives: Results From a Deliberating Public

Abstract: Public deliberation offers a method to probe informed constituent views of how a hospital can best promote its community's health. Informed local residents felt that hospitals should frame health-promoting activities more broadly than is current practice. Not-for-profit hospitals gain significant tax advantages. Increased insurance rates suggest that some hospitals will experience savings in uncompensated care that can be used to promote health more broadly. Vetting priorities for the use of new resources with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Other studies emphasized the effect the CHNA process has on community members. Gold et al studied a public deliberation with Maimonides Medical Center in Brooklyn, NY and found that the participants emerged with greater knowledge of community health and 95% thought hospitals should use public deliberation to identify priority needs (71). Kuehnert, Graber, and Stone used a web-based survey, generating quantitative measures with Likert scales and qualitative insights from open-ended questions, to discover that those community members who were directly involved in the CHNA process were more satisfied with the final product than those who did not participate (27).…”
Section: Community Assessment: Effectmentioning
confidence: 99%
“…Other studies emphasized the effect the CHNA process has on community members. Gold et al studied a public deliberation with Maimonides Medical Center in Brooklyn, NY and found that the participants emerged with greater knowledge of community health and 95% thought hospitals should use public deliberation to identify priority needs (71). Kuehnert, Graber, and Stone used a web-based survey, generating quantitative measures with Likert scales and qualitative insights from open-ended questions, to discover that those community members who were directly involved in the CHNA process were more satisfied with the final product than those who did not participate (27).…”
Section: Community Assessment: Effectmentioning
confidence: 99%
“…Hospital-based programs are useful to help provide caregivers with prevention education while they bring their child in for medical services. Specifically, research has found that hospital-based prevention initiatives are not only a part of holistic patient care but are perceived as more accessible for low-income patients with many individuals reporting that they are more willing to attend if they are in a hospital rather than a community setting (Gold et al 2018 ; Peck et al 2016 ). While hospital prevention programs may limit the barriers that exist in community programs, making program information easy to understand is essential for program success.…”
Section: Introductionmentioning
confidence: 99%
“…Participatory decision-making processes that directly engage community members have been widely used in many countries and are gaining in popularity in the United States (Abelson et al, 2003; Cabannes, 2004; Degeling, Carter, & Rychetnik, 2015; Gold, Realmuto, Scherer, Kamler, & Weiss, 2017; Lenaghan, New, & Mitchell, 1996). Approaches such as participatory budgeting and public deliberation have been recognized as effective ways to allocate resources based on community needs and consult with the public about policy and program decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches such as participatory budgeting and public deliberation have been recognized as effective ways to allocate resources based on community needs and consult with the public about policy and program decisions. They also produce solutions that are more likely to be supported and adopted (Cabannes, 2004; Gold et al, 2017; Lasker & Weiss, 2003; Milton et al, 2011; Rifkin, Lewando-Hundt, & Draper, 2000; Roussos & Fawcett, 2000; Wolf et al, 2016). Participatory grant making, a process which allows residents and other stakeholders to be engaged in funding decisions, has many benefits.…”
Section: Introductionmentioning
confidence: 99%